Cluster analysis of phenotypes of patients with Behçet’s syndrome: a large cohort study from a referral center in China - Zou, Jun; Luo, Jian-feng; Shen, Yan; Cai, Jian-fei; Guan, Jian-long (Arthritis research & therapy, 2021)
Behcet's syndrome (BS) is a complex, heterogeneous disorder. However, classification of its subgroups is still debated. The purpose of this study was to investigate the clinical features and aggregation of patients with BS in China, based on manifestations and organ involvements. This was a cross-sectional study of BS patients in Huadong Hospital of Fudan University between September 2012 and January 2020. We calculated relative risks (RRs) of clinical variables according to sex. Moreover, we conducted a hierarchical cluster analysis applied according to eighteen variables to determine subgroups of patients. A total of 860 BS patients were included. Male sex was associated with ocular involvement (RR 2.32, 95% CI 1.67, 3.22, P < 0.0001), vascular involvement (RR 2.00, 95% CI 1.23, 3.23, P = 0.004), cardiac lesion (RR 5.46, 95% CI 2.33, 12.77, P < 0.0001), and central nervous system involvement (RR 2.95, 95% CI 1.07, 6.78, P = 0.007) and was negatively associated with genital ulcers (RR 0.84, 95% CI 0.79, 0.91, P < 0.0001). Five clusters (C1-C5) were observed. C1 (n = 307) showed the skin and mucosa type. In C2 (n = 124), all had articular involvement, barely having major organ involvement except for 18 cases with intestinal lesions. In C3 (n = 156), the gastrointestinal type, 144 patients presented with intestinal involvement, and 36 patients with esophageal ulcers. In C4 (n = 142), all subjects presented with uveitis. C5 (n = 131) consisted of 44 patients with cardiac lesions, 58 with vascular involvement, and 26 cases having central nervous system involvement. Our analysis confirmed sex differences in phenotypes of BS. Cluster analysis identified gastrointestinal, uveitis, and cardiovascular involvement cluster separately in different subsets, which represents the most commonly involved organs. Further research is required to replicate and clarify the patterns of phenotype in BS.